Polysialic Acid in the Immune System - Villanueva-Cabello, Tania M.; Gutiérrez-Valenzuela, Lya D.; Salinas-Marín, Roberta; López-Guerrero, Delia V.; Martínez-Duncker, Iván (Frontiers in Immunology, 2022)
Polysialic acid (polySia) is a highly regulated polymer of sialic acid (Sia) with such potent biophysical characteristics that when expressed drastically influences the interaction properties of cells. Although much of what is known of polySia in mammals has been elucidated from the study of its role in the central nervous system (CNS), polySia is also expressed in other tissues, including the immune system where it presents dynamic changes during differentiation, maturation, and activation of different types of immune cells of the innate and adaptive response, being involved in key regulatory mechanisms. At least six polySia protein carriers (CCR7, ESL-1, NCAM, NRP2, ST8Sia 2 and ST8Sia 4) are expressed in different types of immune cells, but there is still much to be explored in regard, not only to the regulatory mechanisms that determine their expression and the structure of polySia chains, but also in the identification of the cis- and trans- ligands of polySia that establish signaling networks. This review summarizes the current knowledge on polySia in the immune system, addressing its biosynthesis, tools for identification and structural characterization, as well as its functional roles and therapeutic implications.